Archaeological manifestations of the bishops in Greater Mercia, AD 700-950 - Varley, Rose (2021)
The rise of the Minster Hypothesis, put forward by John Blair (2005) and others (e.g. Foot 2006; Tinti 2005) has led to archaeological research focusing on the impact of the monasteries as institutions in the provision of pastoral care and as centres of economic centrality during Anglo-Saxon England. Although this model has contributed to the increasing archaeological investigations at Middle Saxon sites across Mercia, it undermines the importance of the individual bishops during this period, and has led to some academics calling out for a reassessment of the role of the bishops in the early English Church (e.g. Coates 1996). The following research, therefore, aims to highlight how the evidence can be used to explore bishops in Anglo-Saxon society, especially in regards to the geographical distributions of power and the archaeological manifestations of trade. In order to explore these themes, the following paper will have a mixed methodology of archaeological and documentary evidence and will focus on the region of Greater Mercia between the period of AD700-950.